OFFSHORE PIPELINE RISKAND CONSEQUENCE ASSESSMENT (Jurnal Mekanikal, 2018)
There are several modes of transporting oil produced offshore to theprocessing site onshore. In doing so there are risks that oil spill mighthappen. In this paper offshore pipeline as a mode of transporting oilf rom an offshore Oilfield to the landfall site is being considered. Thestudy also concerns the impact on the environment fromthe sources ofdamage to the subsea pipe line to the landfall site. Mitigative measuresin the event ofoil spills are also discussed. In addition hazard that areassociated with the operational phase of the project are alsoidentified.
Keywords: Keywords